Genetic evidence for the causal effect of clonal hematopoiesis on pulmonary arterial hypertension - Jia-Yong Qiu; Shen-Shen Huang; Chao Liu; Dong Ding; Yan-Hong Xu; Yi-Min Mao; Ya-Dong Yuan (BMC Cardiovascular Disorders)
Abstract Background Pulmonary arterial hypertension (PAH) is a severe and progressive cardiovascular disease. While potential links between clonal hematopoiesis (CH) and cardiovascular diseases have been identified, the causal relationship between CH and PAH remains unclear. This study aims to investigate the causal effect of CH on the risk of PAH using a two-sample Mendelian randomization (MR) approach. Methods We utilized genetic variants associated with CH as instrumental variables, identified from two large genome-wide association studies (GWAS) involving 359,088 participants in the discovery cohort and 184,121 participants in the validation cohort, all of European descent. We obtained GWAS summary statistics for PAH. The inverse-variance weighted (IVW) method was employed as the primary analysis, complemented by sensitivity analyses to assess the robustness of our findings. A bidirectional MR analysis was conducted to estimate the causation between CH and PAH. Results Our results indicate a causal effect of CH on the risk of PAH in the discovery cohort, with TET2 showing an IVW odds ratio (OR) of 1.200 (95% CI: 1.001–1.438, P = 0.049). Sensitivity analysis did not reveal significant pleiotropy or heterogeneity. In the validation cohort, we found that TET2 remains a risk factor for PAH (OR = 2.3E + 08, 95% CI 17.007-3.1E + 15, P = 0.022). Additionally, no causal relationship was found between other CH genes, such as DNMT3A and PAH (P > 0.05). The reverse MR analysis provided no evidence of causal effects of PAH on CH. Conclusion These findings showed that individuals with CH due to TET2 mutations may have a higher risk of developing PAH, suggesting that the CH patients may be tested for TET2 gene mutations.